Approximation of classes of analytic functions by a linear method of special form - Serdyuk, A. S.; Chaichenko, S. O. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
On classes of convolutions of analytic functions in uniform and integral metrics, we find asymptotic equations for the least upper bounds of deviations of trigonometric polynomials generated by certain linear approximation method of a special form.